Multiple corticosteroid abnormalities in cats with hyperaldosteronism. (31st July 2021) - Langlois, Daniel K.; Mazaki‐Tovi, Michal; Harro, Cailin C.; Refsal, Kent R.
Abstract: Background: The frequency with which multiple corticosteroid abnormalities occur in cats with aldosterone secreting adrenocortical tumors is unknown. Objectives: To evaluate adrenal‐derived corticosteroids in cats in which blood samples were submitted for measure of aldosterone. Animals: Two hundred ninety‐seven cats. Methods: Retrospective study. Analysis of a convenience sample of previously submitted serum or plasma. Progesterone, corticosterone, and cortisol were measured in feline serum or plasma samples submitted to an endocrinology laboratory for aldosterone measurements. Demographics and clinical history were retrieved from submittal forms when provided. Statistical testing was performed to investigate associations among the adrenal corticosteroids. Results: Progesterone and corticosterone concentrations were strongly correlated ( ρ = 0.74; P < .001). Progesterone (median, 5 nmol/L; interquartile range, 3‐10 nmol/L) and corticosterone (113 nmol/L, 38‐250 nmol/L) in cats with markedly increased aldosterone concentrations (≥3000 pmol/L) were higher than progesterone (1 nmol/L, 1‐2 nmol/L) and corticosterone (12 nmol/L, 3‐25 nmol/L) in cats with normal aldosterone concentrations ( P < .001 for both comparisons). Progesterone concentrations ≥10 nmol/L (normal, ≤2 nmol//L) occurred in 24 of 76 (32%) cats with aldosterone concentrations ≥3000 pmol/L. Cortisol was lower in cats with aldosterone concentrations ≥3000 pmol/L as compared to those with aldosterone concentrations <500 pmol/L (59 nmol/L, 27‐103 nmol/L vs 103 nmol/L, 49‐182 nmol/L; P = .002). Conclusions and Clinical Importance: Multiple corticosteroid abnormalities occur in a subset of cats with hyperaldosteronism. The magnitude of increases in progesterone and corticosterone in some cats with hyperaldosteronism is likely to be clinically relevant.